Gastrointestinal transit tolerance, cell surface hydrophobicity, and functional attributes of Lactobacillus Acidophilus strains isolated from Indigenous Dahi. Issue 9 (13th July 2021) - Farid, Wajiha; Masud, Tariq; Sohail, Asma; Ahmad, Nazir; Naqvi, S. M. Saqlan; Khan, Sipper; Ali, Amjad; Khalifa, Salah A.; Hussain, Abid; Ali, Sartaj; Saghir, Maryum; Siddeeg, Azhari; et al.
Abstract: Strains of Lactobacillus acidophilus WFA1 (KU877440), WFA2 (KU877441), and WFA3 (KU877442) were isolated from indigenous Dahi (yogurt), screened, and selected based on acid and bile tolerance along with the antimicrobial activity. These selected strains were further assessed for their probiotic and functional attributes. Results for simulated gastric and intestinal tolerance/ resistance revealed that all three strains can resist and survive under the following mentioned conditions. To access cell surface hydrophobicity, bacterial adhesion to hydrocarbons (BATH), cellular auto‐aggregation, and salt aggregation were performed. In BATH, adhesion of strains against three hydrocarbons namely xylene, dichloromethane, and hexadecane was conducted. The results show that strains showed the least adhesion to xylene (54.25%) as compared to dichloromethane (55.25%) and hexadecane (56.65%). WFA1 showed maximum adherence percentage (55.48%) followed WFA2 (55.48%) and WFA3 (51.38%). Cellular auto‐aggregation varied from 21.72% to 30.73% for WFA3 and WFA1, respectively. In the salt aggregation test (SAT), WFA1, WFA2, and WFA3 aggregated at 0.6, 1.0, and 2.0 molar concentrations of ammonium sulfate, respectively. PCR amplification of bile salt hydrolase gene (bsh) was performed and sequences were submitted to the public database of NCBI and Gene bank under accession numbers, KY689139, KY689140, and KY689141. Additionally, a cholesterol‐lowering assay was conducted and up to 26% reduction in cholesterol was observed by the strains. Regarding functional properties, exopolysaccharide (EPS) production, and antioxidant potential, strain WFA1 showed promising results EPS (1.027mg/ml), DPPH (80.66%), ABTS (81.97%), and reducing power (1.787). It can be concluded from the present study that the mentioned strains of L. acidophilus (WFA1, WFA2, and WFA3) are strongly hydrophobic; thus having an ability to survive and colonize under the gastrointestinal tract which confirms their probiotic nature. Regarding their functional properties, L. acidophilus WFA1 (KU877440) showed excellent properties of antioxidants and EPS production. Abstract : Strains of L. acidophilus (WFA1, WFA2 and WFA3) have resisted and survived under GI tract conditions, furthermore; they have the capability to adhere and colonize in the intestinal cavity, thereby confirming their probiotic potential. These strains also have cholesterol‐lowering property along with high EPS production and antioxidant activity. Among the three strains, WFA1 was selected further due to its potential functional properties and was supplemented to produce probiotic fermented milk.